Edukasi MP-ASI Memberikan Bekal Pengetahuan dan Keterampilan Bagi Ibu - Septyasih, Rossyana; Prastiwi, Swito; Wahyuni, Eko Sari (Jurnal Keperawatan Terapan, 2025)
Malnutrition that occurs in infants can be fatal, which can inhibit growth and development and can even occur in the long term. The age period of 6-24 months in children is the golden period for complementary feeding, because this is the critical phase for providing interventions related to child nutrition. Mothers’ ability to provide complementary feeding is very important to prevent nutritional problems in children. This study aims to determine the ability of mothers to provide complementary food after being given education. This study used a descriptive case study method conducted on two mothers who acted as research subjects. Data collection in the study was carried out through interviews, questionnaires, and observations, namely before and after being given education. The results of this study showed that before education, the ability of the two research subjects was still lacking in aspects of knowledge, attitudes and actions related to complementary feeding. After being given education, there was a significant increase in all three aspects. The conclusion that can be drawn from the study is that education is proven to be effective in improving mothers’ ability to provide complementary foods. Subjects are expected to consistently apply the knowledge that has been obtained related to complementary feeding properly and correctly. Future research is expected to develop a more in-depth observation method to examine mothers’ ability to provide complementary foods, including the process of preparing, making, serving, and feeding complementary foods.